Realizing the promise of chemical glycobiology - Wang, L; Davis, B (Royal Society of Chemistry, 2013)
Chemical glycobiology is emerging as one of the most uniquely powerful sub-disciplines of chemical biology. The previous scarcity of chemical strategies and the unparalleled structural diversity have created a uniquely fertile ground that is both rich in challenges and potentially very profound in implications. Glycans (oligosaccharides, polysaccharides, and glycoconjugates) are everywhere in biological systems and yet remain disproportionately neglected - reviews highlighting this 'Cinderella status' abound. Yet, the past two decades have witnessed tremendous progress, notably in chemical and chemoenzymatic synthesis, 'sequencing' and arrays, metabolic engineering and imaging. These vital steps serve to highlight not only the great potential but just how much more remains to be done. The vast chemical and functional space of glycans remains to be truly explored. Top-down full-scale glycomic and glycoproteomic studies coupled with hypothesis-driven, bottom-up innovative chemical strategies will be required to properly realize the potential impact of glycoscience on human health, energy, and economy. In this perspective, we cherry-pick far-sighted advances and use these to identify possible challenges, opportunities and avenues in chemical glycobiology.